SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMPREDIKSI PENJUALAN PADA TOKO JEK YEK SIANG - Ong, Ricky; Harman, Rika (LPPM Universitas Putera Batam, 2022)
Various business or shops that have used computer technology such as a computerized system of buying and selling processes, this shows that computer technology has developed rapidly. One of the shops that have used a computerized system in the buying and selling process is the Jek Yek Siang shop. Data collection was done by interview and direct observation at the location, the purpose of this study was to find out the best-selling items and to be able to arrange the layout strategy of the goods that could increase sales. This study uses the association method to look for patterns of interrelationships between items that appear the most in data transactions. The process of determining the pattern of purchasing goods is carried out using data mining with the a priori algorithm method, so that the results in the case of the Jek Yek Siang shop are the highest that appear in the Cendana Incese and Cap Merak Tea items with a support value of 26.7% and a confidence value of 100%.